Exumando verdades: As vítimas insepultas do Regime Militar do Estado da Paraíba - Figueiredo, Marx Igor Ferreira (2016)
The present study proposes to analyze the cases of forced disappearances of Paraibans during the Military Dictatorship and their possible relation with the actions of the repression organs. To this end, a brief study of the historical moment before the military coup, which had the logistical and strategic support of the United States of America, is undertaken, and it is in the post-coup moment that the consequences are verified that the regime Military brought to the country, subject to observation of the changes brought by each government, especially in relation to the coexistence with freedoms. Next, there is an exposition of conceptual and historical aspects related to Transitional Justice, emphasizing the normative evolution of the instruments of transitional justice and their importance in the process of recovery of historical memory and national reconciliation. Finally, the six cases of forced disappearances of Paraiban during the military regime, listed in the first report of the State Truth Commission, are studied. In this chapter, in addition to checking the profiles of each victim and their possible involvement in resistance movements, the performance of the repressive organs, the characteristics of each agent of repression that were in front of these units and the ways in which the bodies Of those considered subversive were hidden or discarded. It is a research of a qualitative nature, whose methodological design will be, as a matter of priority, bibliographical, survey, documentary and case study, since it will have as the north the six cases of disappearance listed by the State Commission of Truth.